Predictors of Employee Performance Based on Discipline, Competence, and Organizational Culture (Case Study of Sub-Village and Village Employees in Kota Raja Village, Kupang City Government) - Fenilom Muday; Luis Marnisah; Tien Yustini; Jefirstson Richset Riwukore (Institute of Computer Science (IOCS), 2022)
This research aimed to analyze and prove the effect and contribution of discipline, competence, and organizational culture to employee performance. This research was carried out for 5 months from February to June 2022 at the Subvillage Office and Village Office in the Kota Raja Village, Kupang City. This research is classified as quantitative research. The research population was 103 employees who were determined by the sample of respondents using a saturated sample (non-probability sampling) so that the entire population became research respondents. The types of data used are primary and secondary data obtained by questionnaire, observation, and documentation techniques. Data analysis used multiple linear regression analysis. The results showed that the discipline variable had a positive and significant effect on employee performance because it had t-count > t-table (9,165 > 1,98373) on Sig. Prob. 0.000 < α 0.05. Competence variable has a positive and significant effect on employee performance because the value of t-count > t-table (7.176 > 1,98373) in Sig. Prob. 0.000 < α 0.05. The organizational culture variable has a positive and significant effect on employee performance because the t-count > t-table (4,807 > 1,98373) in Sig. Prob. 0.000 < α 0.05. Simultaneously, all variable were a positive and significant effect on employee performance because the value of F-count > F-table (31.013 > 2,69) in Sig. Prob. 0.000 < α-0.05. Kontribusi setiap variabel independen terhadap kinerja pegawai mulai dari yang tertinggi ke terendah adalah variabel disiplin (51,8%), budaya organisasi (15,4%), dan kompetensi (11,9%).